Landmarks in humanities - Fiero, Gloria K. (2017)
"Landmarks in Humanities is a single-volume survey of global culture designed to help students of humanities, cultural history, and history of the arts to understand and appreciate the relevance of historical works and ideas to their own daily lives. In chronological sequence, Landmarks guides students on a journey of the most notable monuments of the human imagination and the most prominent ideas and issues that have shaped the course and character of the world's cultures from prehistory to the present. The landmarks that mark this journey are the great works of their place and time and, in some cases, of all time. The text reflects the author's extensive background in the study of Humanities, which has enabled her to craft a narrative that is at once brief and comprehensive, giving students a thorough understanding of the interrelatedness of various modes of expression--art and architecture, literature, philosophy, and music--without overwhelming them with detail. Each of the text's fifteen chapters is centered on a key idea related to the period being discussed, and contains a series of valuable pedagogical features including timelines, high-quality maps, and boxed material. Each chapter also takes a unique cultural or historical point of view, often through primary sources, the stylistic relationship between two or more images and ideas or between text and image, and contemporaneous non-Western cultural landmarks and cross-cultural influences. In this edition, each chapter opens with 'A First Look' at a landmark work that illustrates the key idea of the chapter and acts as a cultural guidepost to that chapter's overarching theme. This new feature explains the artwork's significance as a landmark in its own time as well as in ours"--
12. Romanticism : Nature, Passion, and the Sublime -- Heralds of Romanticism -- Romantic Literature -- American Romanticism -- Romanticism in the Visual Arts -- Romantic Music and Dance -- Beyond the West: Exploring Africa -- Afterword -- Key Topics -- Romanticism Timeline -- 13. Materialism : The Industrial Era and the Urban Scene -- The Global Dominion of the West -- Literary Realism -- Late-Nineteenth-Century Architecture -- Realism in the Visual Arts -- Impressionism -- Postimpressionism -- Beyond the West: The Lure of the Exotic : Oceania -- Late-Nineteenth-Century Sculpture -- Late-Nineteenth-Century Music -- Afterword -- Key Topics -- Materialism Timeline -- 14. Modernism : The Assault on Tradition -- New Directions -- War and Revolution -- Beyond the West: Mao's China -- Modern Literature -- Modern Art -- Modern Architecture -- Music and Dance -- Afterword -- Key Topics -- Modernism Timeline -- 15. Globalism : Information, Communication, and the Digital Revolution -- Post-War Convulsions -- The Quest for Equality -- Science and Philosophy -- The Information Explosion -- Contemporary Literature -- Art and Architecture -- Music and Dance -- Into the Twenty-First Century -- Afterword -- Key Topics -- Globalism Timeline -- Glossary.
Includes bibliographical references and index.
Keywords: Civilization -- History -- Textbooks; SOCIAL SCIENCE / General